The Psychometric Properties of the Norwegian version of Social Communication Questionnaire (SCQ) - Kaasbøll, Jannike; Jozefiak, Thomas; Aanondsen, Chris Margaret (PsykTestBarn, 2021)
Description: The Social Communication Questionnaire (SCQ) is an assessment tool designed to identify children who may be on the autism spectrum. The original British SCQ, developed by Rutter, Bailey, and Lord in 2003, was translated into Norwegian by Synnøve Schjølberg and Kristian Tambs. The SCQ is available in two forms – Lifetime and Current – composed of 40 yes or no questions each. Both forms are given directly to the parent or primary caregiver and are completed within 10 minutes. The SCQ can be administered by psychologists, doctors, social workers, nurses, special needs teachers, or speech and language, occupational, and physical therapists. The Norwegian version is available from Hogrefe Psykologiförlaget AB. Literature search: A total of 301 articles were identified based on a systematic literature search, 13 of these were from Scandinavian countries and were included. Four of these 13 articles are based on small samples with specific syndromes. Psychometrics: Means and standard deviations were reported in most studies. There are no Norwegian or Scandinavian norms or reports on construct or convergent validity. Only one of the studies reports internal consistency. Conclusion: The psychometric properties of the Norwegian version of the SCQ have, so far, not been sufficiently examined.